The physicochemical properties, bioactive composition, bioactivity, and food innovation based on Flacourtia inermis fruit: A narrative literature review - Witoyo, Jatmiko Eko; Alvianto, Dikianur; Permatasari, Nelsy Dian; Utoro, Panggulu Ahmad Ramadhani (Journal of Food and Agricultural Product, 2025)
Flacourtia inermis fruit, locally known as lobi-lobi fruit, is one of Indonesia's rare local fruits, rich in nutritional and bioactive compounds. However, the physical-chemical characteristics, bioactive composition, bioactivity, and food innovations based on the lobi-lobi fruit have not yet been comprehensively explored. So, the objective of this article is to provide a comprehensive overview of the physical-chemical characteristics, bioactive composition, bioactivity, and food innovations based on the lobi-lobi fruit, as per earlier studies. The approach used in this study is a narrative literature review, with data sources comprising earlier publications, including articles and scientific proceedings from 2011 to 2025, that are relevant to the topic under discussion. The review findings revealed that fresh lobi-lobi fruit is characterized by its high moisture, fat, and vitamin C content, as well as its richness in various phytochemical compounds, including tannins, saponins, flavonoids, phenolics, triterpenoids, alkaloids, and anthocyanins. Numerous studies have demonstrated that lobi-lobi fruit and its extracts exhibit significant bioactivities, such as antioxidant, antibacterial, antidiabetic, anti-hypertension, acting as a lipase enzyme inhibitor, and a remedy for dyslipidemia. Innovations deriving from lobi-lobi fruit include the production of vinegar and wine, alongside its application as a natural preservative for fishery products and a flavoring agent in food products. Looking ahead, there is considerable potential for lobi-lobi fruit to be utilized for fortification and supplementation in food products, as well as being processed into powder form through drying to enhance its shelf life and accessibility. Keywords: bioactive, bioactivity, food innovation, lobi-lobi fruit, physicochemical characteristics